Discovering Action Research: the Evolution of My Research Question - Barbara Bell Angus (Networks: An Online Journal for Teacher Research, 2003)
As a new member of Developing Inquiring Communities in Education Project (DICEP) as well as a rookie action researcher, I feel that my greatest contribution at this time is to chronicle the evolution of my research question through my initial cycle of action research. I hope this article will provide encouragement to other first time action researchers as they wrestle with their initial projects.